Pengembangan Media Pembelajaran Board Game Aksara Jawa Kelas III SDN 2 Bandung Prambon - Widyaningrum, Deviyanti; Permana, Erwin Putera; Kurnia, Ita (Universitas Nusantara PGRI Kediri, 2024)
Javanese is the language we use in everyday life. This must be preserved and studied by the nation's future young generation so that this culture is not eroded by foreign culture. Many students think that the Javanese script material is very difficult. This is because there is no Javanese script learning media available that supports learning, students think that the Javanese script material is very difficult, and students also find it difficult to memorize and read Javanese script letters because they are not used to writing and reading Javanese script and Javanese script letters have several similarities. one letter to another. This research aims to determine the importance of Javanese script board game learning media for class III. The type of research is the development research method or RnD (Research and Development) and the techniques used for data collection are observation, questionnaires, tests, documentation. At SDN 2 Bandung, Prambon researchers distributed questionnaires to several parties. The learning media developed is a Javanese script board game. This media has gone through a validation stage carried out by media expert validation and material expert validation. Based on the validation results, media experts obtained a validity percentage of 83% and material expert validation obtained a percentage of 97%. From these two validations, the final validity score was 90%, the validity criteria were in the range 81.00%-100.00% with a validation level of